Northern Ireland and the crisis of anti-racism : Rethinking racism and sectarianism - Gilligan, Chris (Book collections on Project MUSE., 2017)
Racism and sectarianism makes a sustained critique of official anti-racism. The book, uniquely, uses the case of Northern Ireland to do so. Many of the prominent themes in the UK today - the role of religion in 'race', racism and 'terrorism', community cohesion - have been central to discussions in Northern Ireland for decades. The book sketches out some elements of an emancipatory anti-racism as an alternative.